2014
DOI: 10.1517/14728222.2014.934813
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin as a regulator and therapeutic target for asthmatic airway remodeling

Abstract: The aberrant activation of β-catenin signaling by both WNT-dependent and -independent mechanisms in asthmatic airways plays a key role in remodeling the airways, including cell proliferation, differentiation, tissue repair and extracellular matrix production. These findings are interesting from both a mechanistic and therapeutic perspective, as several drug classes have now been described that target β-catenin signaling directly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 86 publications
3
47
0
3
Order By: Relevance
“…Toward developing a mechanistic understanding of the effects of insulin on the lung, we show that ␤-catenin signaling is enhanced by insulin in vitro and in vivo. ␤-Catenin has been previously implicated in cell proliferation and EMT (22,30). Previous studies have also confirmed the role of ␤-catenin in ASM cell contraction (18).…”
Section: Discussionmentioning
confidence: 64%
“…Toward developing a mechanistic understanding of the effects of insulin on the lung, we show that ␤-catenin signaling is enhanced by insulin in vitro and in vivo. ␤-Catenin has been previously implicated in cell proliferation and EMT (22,30). Previous studies have also confirmed the role of ␤-catenin in ASM cell contraction (18).…”
Section: Discussionmentioning
confidence: 64%
“…Those decreased in expression are involved in the extracellular matrix, and the whole profile is important for cellular assembly (Fig 1, A ). Interestingly, hydrolase activity is known to be important for calcium signaling in ASM, 9 and the extracellular matrix is involved in asthmatic airway remodeling 10 . In the ASMCs from the patients with severe asthma, these profiles changed to an increase in genes necessary for arachidonic acid metabolism and a decrease in those required for multicellular organismal process, and the whole profile is involved in gene expression and organ morphology.…”
Section: Resultsmentioning
confidence: 99%
“…Of the mRNAs we examined, we found that the mRNA profile differentially regulated in ASMCs from patients with nonsevere asthma is important in ASMC calcium signaling, 9 airway remodeling, 10 the inflammatory response, 13 and glucocorticoid activity 15, 16. Interestingly, the mRNA profile in ASMCs from patients with severe asthma appears to be important in increased calcium influx in the smooth muscle, 11 atopy, 12 and possible immunomodulation in patients with acute exacerbations of airway disease, including asthma 14 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that ~90% of cases of colon cancer were associated with excessive activation of this pathway (4). β-catenin is the key molecule of the Wnt/β-catenin signaling pathway (5). Thus, silencing the β-catenin gene may inhibit the development and invasion of colon cancer.…”
Section: Introductionmentioning
confidence: 99%